2003
DOI: 10.1109/jstqe.2003.813316
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost microoptical modules for mcm level optical interconnections

Abstract: A multi-channel free-space micro-optical module for dense MCM-level optical interconnections has been designed and fabricated. Extensive modeling proves that the module is scalable with a potential for multi-Tb/s.cm 2 aggregate bit rate capacity while alignment and fabrication tolerances are compatible with present-day mass replication techniques. The micro-optical module is an assembly of refractive lensletarrays and a high-quality micro-prism. Both components are prototyped using deep lithography with proton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…Though random interconnect patterns are difficult for free-space optics, regular structures such as busses or even strongly interleaved patterns such as perfect shuffles that are suited to operations such as Fourier transforms or switching networks could be quite viable. Micro-optical systems can make free-space connections from chip to chip or within a chip [112], and a planar optics technology has been demonstrated that could make entire pre-aligned "free-space" optical systems based on lithography on a planar substrate [111].…”
Section: B)mentioning
confidence: 99%
“…Though random interconnect patterns are difficult for free-space optics, regular structures such as busses or even strongly interleaved patterns such as perfect shuffles that are suited to operations such as Fourier transforms or switching networks could be quite viable. Micro-optical systems can make free-space connections from chip to chip or within a chip [112], and a planar optics technology has been demonstrated that could make entire pre-aligned "free-space" optical systems based on lithography on a planar substrate [111].…”
Section: B)mentioning
confidence: 99%
“…• C. The detailed physics behind technological processing steps have been published before [26]- [28]. We demonstrated that DPW is a flexible technology to fabricate 2D matrices of spherical microlenses with different diameters between 120 and 200 µm and focal numbers ranging from 1 to 7 on the same PMMA substrate.…”
Section: The Swelling Processmentioning
confidence: 99%
“…We have shown that this type of interconnect modules has the potential to provide the highly desirable massive parallel highspeed interconnects needed for future generations intra-MCM level interconnections [28]. We are currently working towards a massively parallel intra-chip interconnect demonstrator that will carry a channel density above 4000 channels cm −2 and hence provide us with low-cost, chip compatible, plug-and-play, commercially viable interconnect solutions [39].…”
Section: Intra-mcm Interconnect Modulementioning
confidence: 99%
“…One can cite, for example, passive alignment of micro-Fresnel lens arrays with side-mounted VCSELs [19]. A low-cost plastic multichannel interconnection module including a lenslet and a high-quality microprism was also successfully developed for increasing misalignments tolerances to ±40 µm (Figure 4) [20].…”
Section: Passive Micro-optics For Vcsel: Hybrid Assemblymentioning
confidence: 99%